Efficiency Assessment of Indian Passenger Airlines Using Two-Stage Efficiency Model: Non Traditional DEA Approach. (3rd September 2021) - Seth, Bharti; Saxena, Punita; Arora, Shalini
ABSTRACT: Indian airline industry has been facing the financial and operational challenges for the last many years. The challenges have increased many folds due to the ongoing pandemic. Many of the airlines are struggling for their survival, and therefore, there is an utmost need of redesigning the business model for this industry. The objective of this study is to define a two-stage data envelopment analysis (DEA) model for the airline industry to promote a smooth coordination between its two internal operational stages. The proposed two-stage DEA model is among the foremost and eloquent effort in evaluating the performance of two stages. Stages I and II are defined in accordance with the working process of airlines. Efficiency of Stage I is called the structural efficiency, while that of Stage II is called an operational efficiency. The proposed model is defined with three types of inputs, one intermediate and two types of output variables. The model has been illustrated for eleven airlines operating in India for the year 2017–18. This study will help the decision makers in assessing the airline's performance with an identification of factors that are responsible for their poor performance. The study also suggests the percentage of operating cost that can be optimally shared between two stages.